ENVIRONMENTAL TAXION TRENDS IN EUROPE - KOZIUK, Viktor; SHYMANSKA, Oksana; VOZNYI, Kazymyr (Scientific journal «World of Finance», 2020)
Introduction. EU countries are showing an increasing trend towards the priority of the public good “clean ecology”. Environmental taxation not only exerts fiscal, but above all, corrective influence on the behavior of economic agents. Nonetheless, the fiscal design of environmental taxes and their composition as a source of budget revenue remains an issue that needs further study. Purpose is to track current environmental tax trends in Europe, the evolution of environmental policy instruments in EU countries, to analyze their economic and social impact; to identify problems with the existing environmental taxation system in Ukraine. Methods. In researching current environmental tax trends in Europe, identifying the stages of evolution of environmental policy instruments, analyzing their impact on the economy and social sphere, substantiating the problems of the existing system of environmental taxation in Ukraine, a number of scientific and special methods of research were used, in particular: analysis, synthesis, induction, deduction, abstraction, generalization, statistical, graphic, tabular. Results. Based on the analysis of the dynamics of different types of environmental taxes in the EU-28 countries for the period 1995–2017 (gross, energy, transport, pollution taxes, resources), a general tendency for their increase was revealed. In a comparative analysis of growth dynamics of total environmental taxes (TET), taxes on CO2 and greenhouse gases in the same sample of countries during the study period, a tendency was found to exceed the growth rate of TET over the reducing harmful emissions, which confirms the implementation of environmental taxes fiscal function, than corrective one. It has been stated that, despite the coherence and systematic nature of European countries’ environmental tax policy, compensating for “environmental losses” indirectly increases its sensitivity to public sector efficiency and breaks the link between environmental taxation and the public good “clean ecology”. At the same time, problems were identified in the field of environmental taxation in Ukraine, in particular to the lack of an effective model of taxation, due to the inconsistency of the revenue mechanisms and proportions of the distribution of environmental taxes between budgets of different levels. Conclusions. Further research suggests focusing on assessing efficiency level of the environmental tax system in European countries, which will create the basis for improving the latter in Ukraine.